Reaching and Responding to the Audience - Catlin-Legutko, Cinnamon; Klingler, Stacy (Rowman & Littlefield Publishers, 2011)
Museums exist to serve their audiences; however, the scope of this charge is constantly being challenged and changed. This book looks at new roles small museums have taken as they find ways to become irreplaceable members of the community, engaging with and advocating for their audience—from large-scale marketing and public relations efforts to welcome signs and entrances. Book Five encourages small museums to examine their audiences and make them comfortable, program to their needs and interests, and spread the word about the museum’s good work. It also features several case studies of successful evaluation programs, sample press releases, accessibility checklists, visitor experience checklists and more.